Princess Posey and the flower girl fiasco - Greene, Stephanie (Greene, Stephanie. Princess Posey, first grader., 2018)
Posey is excited that Gramps and her neighbor, Mrs. Romero, are getting married, but unhappy that Mrs. Romero and her dog will move away.